Two new species of nopal (Opuntia, Cactaceae) from the Baja California Peninsula (Mexico) - Muñoz, Fermín Mercado; León De La Luz, José Luis; Rebman, Jon P.; Medel Narváez, Alfonso; Campos Ramos, Rafael (Phytotaxa, 2021)
Two new species of prickly-pear/nopal (Opuntia sierralagunensis and O. caboensis, Cactaceae) are described and illustrated here; both occur in the tropical deciduous forest plant community found in the Cape region of the Baja California Peninsula, Mexico. Previously, these two species had been overlooked and were considered extreme forms of species described from the Sierra de La Giganta (e.g., O. comonduensis, O tapona), located hundreds of kilometers away. However, with an improved collection of specimens and field knowledge of the Opuntia species in the region, we have determined that these prickly-pears are new to science and are restricted to the Cape region. We provide justification to separate them from sympatric congeners and other similar species in the southern peninsula.